NTO . miesięcznik NSZZ "Solidarność" Region Mazowsze, no. 22, 1981 - "Solidarność", [ed. Agnieszka Maciejowska et al.] (NSZZ "Solidarność" Region Mazowsze, 1981)
Creation and circulation: For internal use